Journey of light - Yusof, Zeenat Begam; Mohd. Din, Shamzani Affendy; Mohd. Yaman, Maheran; Mohyin, Nur Affah; Mohamad Suhaimi, Mohamad Saifulnizam (IIUM Press, 2023)
The Journey of Light is the concept adopted for a project under AQS 1301 Multidisciplinary Project, a core course of the Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM). This project aims to revitalize the Al-Ghazali Road located in IIUM Gombak Campus. The Al Ghazali Road is the famous secondary road in IIUM, with several commercial facilities. The road issue is flooding during heavy rain and lacking social and commercial facilities. This project aims to solve the issues by designing the Al Ghazali road using the concept of the Journey of Light in four phases. The four phases indicate Al Ghazali’s contributions to preaching Knowledge throughout his lifetime. The phases are known as Knowledge of God, Knowledge of Self, Knowledge of the World, and Knowledge of the Future World. These phases are distinguished by the different materials used and vegetation based on the Alhambra case studies.